Site investigations and geotechnical assessment for the construction of the deep underground science and engineering laboratory at the former Homestake Mine - SME Transactions 2011 - Z. J. Hladysz; G. D. Callahan; R. Popielak; W. Weinig; C. Randolph-Loar; W. G. Pariseau; W. Roggenthen (Society for Mining, Metallurgy & Exploration, 2011)
A Deep Underground Science and Engineering Laboratory (DUSEL) is being planned at the site of the former Homestake Gold Mine in Lead, SD, under the sponsorship of the U.S. National Science Foundation (NSF) in cooperation with the Department of Energy (DOE). This national facility will host a variety of multidisciplinary science and engineering experiments, including physics experiments that require shielding from cosmogenic radiation. Current plans include construction of large rooms (up to 55 m in width) at depths of 1.48 km (4,850 ft) and 2.25 km (7,400 ft) below the surface. Preparation of the preliminary design required the development of a geotechnical characterization program, including preliminary drilling and coring, core logging, drill hole mapping with a televiewer, drift mapping of the geology and rock structure, in situ stress measurements, and laboratory testing of the mechanical properties of the rocks and discontinuities. Overall rock quality is very good to excellent. Site investigations included geotechnical assessments for the construction of caverns and laboratory modules. The results are favorable and reaffirm selection of the Homestake site for establishment of a Deep Underground Engineering and Science Laboratory.